Artificial Intelligence in Media Discourse of 2010s - A. Yu. Kolianov (Дискурс, 2021)
Introduction. The article examines the image of artificial intelligence in the media and its reflection in 2010s. Coverage of the fast development of technology in the mass media requires careful analysis and systematic monitoring due to not fully determined socio-ethical ideas about the place and role of artificial intelligence in human life. The paper attempts to study what media had about artificial intelligence in the second decade of the 21st century.Methodology and sources. Based on the results of quantitative and qualitative studies of the texts of Russian and foreign media, semantic changes in the representation of artificial intelligence are analyzed. To collect empirical informa tion, we used the analysis of documents (reports and preparatory notes of UNESCO for the development of an ethical code of artificial intelligence), public opinion polls, content analysis of Russian and foreign media.Results and discussion. According to the results of the study, correlation between intensity of references to artificial intelligence on political and economic phenomena was noted. In particular, there is a connection with the growth of economic activity of investors in advanced technologies, the launch of innovative technologies in the sphere of consumption by large companies and the strategic programs of states.Conclusion. At the moment, artificial intelligence is seen as positive technology. Implementation of AI into social and professional spheres is irreversible. The negative consequences of the development of AI are considering as an unobvious hypothetical future. By the beginning of the third decade of the 21st century, the media discourse around AI expanded to such a state of uncertainty that it took action to establish an ethical framework for the development of technology.